Congestion Management Considering Optimal Placement of Distributed Generator in Deregulated Power System Networks - Singh, Kanwardeep; Yadav, Vinod Kumar; Padhy, Narayana Prasad; Sharma, Jaydev (Electric power components and systems, 2014)
This article presents an effective methodology for congestion management in deregulated power system networks considering optimal placement of a distributed generator. The novelty of this method is that the optimal placement of a distributed generator in a deregulated power system is decided on the basis of bus impedance matrix (Z bus ) based contribution factors. The Z bus -based contribution factors are independent of slack bus location, which complies with the prevailing competitive environment. The congestion management problem formulation comprises the maximization of social welfare function subject to power balance and transmission congestion constraints. The maximization of the social welfare function causes maximization of consumer benefits and minimization of supplier generation cost and distributed generators. The proposed methodology has been simulated on an IEEE 30-bus system, and comparisons of results are presented with and without distributed generators. The results show that the proposed approach gives significant improvement in social welfare and decreases congestion rent with distributed generator placement.